Efficacité Du Kaolin (Kalaba) Dans La Gestion Intégrée Des Chenilles Endocarpiques Du Cotonnier Dans La Zone Centre Du Bénin - Bonni, G.; Houndete, T.; Paraïso, A.; Hougni, A. (European Scientific Journal, ESJ, 2017)
The study on the efficacy of Kaolin in the integrated management of the endocarpiques larvae of cotton was undertaken in the center of Benin. The objective of the work was to evaluate the potentiality of Kaolin in the control of some endocarpiques larvae of the cotton plant. To achieve this goal, a Fisher block device with 4 treatments and 4 repetitions were set up on two sites. The treatments developed consisted of an untreated plot ; a plot treated with Lambdacyalothrine 15 g/l - chlorpyrifos ethyl 300 g/l; a plot treated with kaolin 5% and another one with the mixture kaolin + Lambdacyalothrine 15 g/l - chlorpyrifos ethyl 300 g/l. The treatment with kaolin was achieved with a back, maintained pressure sprayer. Ten applications were conducted with the kaolin used alone and 6 with the other objects. Results showed that there is no significant difference between the average number of larvae recorded in the plots treated with kaolin and plots which served as control of reference (Lambdacyalothrine 15 g/l - chlorpyrifos ethyl 300 g/l at 1 l/ha). It was the same for the percentage of attacked green capsules and cotton seed production. The effect of kaolin in the control of Haritalodes derogata was low (11.6% of plants attacked against 0.1 % for the chemical reference control and 22.9 % for the untreated plot). The results of Kaolin associated with the binary acaricide, showed that the number of endocarpiques larvae has been significantly reduced compared to the reference control. This study indicates that kaolin can be used like other biological pesticides, as alternative to chemical control and then, constituted an important component of the integrated cotton pests management.